Sistem Pendukung Keputusan Penentuan Merek Smartphone Terbaik Dalam Mendukung Belajar Online Mahasiswa Era Covid-19 Menggunakan Metode PSI (Preference Selection Index) - Wan Mariatul Kifti; Irene Hasian (STMIK Budi Darma, 2021)
The era of the Covid-19 pandemic has resulted in people having to carry out activities by keeping their distance from one another in order to achieve the termination of the spread of the Covid-19 virus, this activity resulted in the government issuing a decree, especially to the education office to conduct online learning because schools and universities is one of the places that has great potential for easy transmission, online learning makes all students obliged to have a smartphone or android so that it makes it easier for students to access online learning, it is necessary to determine the best smartphone brand with the most purchase criteria, price, capacity owned by smartphone and year. output which will later become a literature review of students and parents of students to be more selective in choosing according to the wishes and needs of each user with the help of a decision support system and the application of the PSI method (Preference Selection Index). rence selection index), and the results obtained with the highest score on the xiaomi smartphone with the highest score of 0,327332, the assessment process is fairer and the decision-making process is fast.